The attitude of teachers towards corporal punishment - Rice, Janet Elizabeth (My University, 2015)
Various educationalists through the ages have expressed concern over, and supported belief in the ineffectiveness of punishment as a disciplinary strategy. Despite the paucity of appropriate research support for its effectiveness and desirability, our society still legalizes the educational use of punishment